STUDI DAN ANALISIS PENYELESAIAN ISU-ISU INTOLERANSI KEAGAMAAN DI SUMATERA BARAT TAHUN 2014-2015 - Silfia Hanani; Nofrianti Putri Utami (Islam Transformatif : Journal of Islamic Studies, 2019)
Religious intolerance in West Sumatra in 2014-2015 experienced an increase which was affected by the rejection of facilities that would be built by investors of different religions with the majority of religious communities. Religious intolerance is an indicator of the low attitude of religious tolerance in society. The phenomenon of racism and theological nuances in Indonesia seems to strengthen the suspicion that religion is the cause of conflict, triggers of violence, and a variety of behaviors that sometimes generate not only hatred, but also hostility, and fierce warfare among humans. However, the case does not cause conflict diversity in this region because of the solutions made for each of these issues. At this time, religious themes have been developed by the community, where people are not easy to accept the religion of Islam that has just been developed by the stranded Arabian sword. After Islam became the official religion of the Minangkabau people in West Sumatra, in general, in West Sumatra, the issue of faith became the part that received attention; the effect of religion meant how to respond to the arrival or emergence of movements outside of the majority religion. This paper describes the solutions made to reduce these issues so as not to cause religious conflict.